Sistematización de La Práctica Pedagógica Relizada en la Escuela Abierta de Arte y Educación Artística con El Grupo de Adulto Mayor (2018)
In this work, the systematization of the pedagogical practice carried out by the teacher is carried out. in training with the older adult group of the Open School of Art and Artistic Education in Antonio Nariño University, in order to dignify the elderly, making visible their creative, ethical and social capacities through artistic work. Here is the description of the entire practice experience and the different dynamics used as methodology for working with the group of older adults and its favorable results during the process. In addition, the social work of the Open School of Art and Artistic Education is highlighted, which has in different contexts and the importance within pedagogical practice, the steps carried out for the systematization, aspects of creative, ethical and socio-affective and physical analysis motor, ending with reflections and conclusion.